How Did COVID-19 Pandemic Stress Affect Poles' Views on the Role of the Forest? - Janeczko, Emilia; Banaś, Jan; Woźnicka, Małgorzata; Janeczko, Krzysztof; Utnik-Banaś, Katarzyna; Zięba, Stanisław; Fialová, Jitka (MDPI AG (Multidisciplinary Digital Publishing Institute-MDPI), 2024)
The 2020-2021 COVID-19 pandemic has had a tremendous impact on the daily lives of everyone, including local communities and entire societies. Under the influence of this new experience, the importance of the services and benefits provided by forests and other green spaces has increased. A very large role in this aspect was played by media messages promoting the idea of being close to nature as a remedy for malaise and stress, and pushing the thesis that the risk of spreading the virus outdoors is lower than it is indoors. Thanks to media messages, as well as government responses (i.e., lockdown, temporary bans on entering the forest), public attention has been directed toward forests, generating greater interest in forest management and conservation issues, as well as in nature and forestry education. The purpose of our research was to determine how the pandemic affected the frequency of visits to the forest and how it changed the public's views on the role of forests. The research material consists of the results of a questionnaire survey (online and traditionally way) carried out in Poland from September to October in 2020. A total of 1402 people were surveyed. The results show that nearly 52% of respondents increased their use of forest recreational services during the COVID-19 pandemic. We also found that more than 80% of respondents agreed with statements that the forest is a safer space than, for example, parks or squares, and it is more difficult to contract the virus there. Men were more likely to agree with this statement than women (1.51), respondents without children (1.45), respondents over the age of 31 (1.72), and respondents with more than primary or secondary education (1.37). Also, more than 80% of respondents said that the social functions of the forest (e.g., recreational) had gained importance as a result of the pandemic. The social functions of the forest gained importance primarily among respondents with higher education (2.40), and among respondents who had visited the forest rather infrequently (several times a year) for recreational purposes before the pandemic (1.72). Those with children were more likely to agree with the statement that the economic functions of the forest have lost their importance (1.43), as were those who had formerly visited the forest several times a year (1.53). With regard to the statement "the slowdown of the economy has contributed to the improvement of the environment," there were no statistically significant differences in the views of respondents in terms of their socio-demographic characteristics.
Keywords: pandemic; forests; ecosystem services; recreation